TATA CARA ADAT PERNIKAHAN MASYARAKAT NIAS DESA ONOWAEMBO KECAMATAN LAHÖMI KABUPATEN NIAS BARAT - Lemsi Suryani Sitorus Suryani Sitorus; Ridwan Melay Melay; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Interest Nias are people who live in the customs and cultures are still high. Nias communities have many cultural one of which is the procedure for a wedding, Wedding in Nias community is very sacred. One important requirement is to pay honesty marriage or dowry. The purpose of this research is to know What are the requirements in the society wedding of Nias village Onowaembo.Untuk know What are the factors that affect the way the people of Nias village wedding Onowaembo.Untuk know how is the wedding procedures performed by the people of Nias village Onowaembo. The method used in this research is descriptive qualitative method. When the study as from the start until the proposal seminar thesis examination. Results from this study is that the marriage ceremony is the Nias community is one of the cultural diversity that comes from Nias tribe. Before choosing a mate advance notice requirements that must be met before the wedding because if these conditions are not met there will be no wedding meal. Marriage in Nias community is also very closely related to the economic, social, especially education. Nias society wedding ceremony begins with the election of a mate (famaigi niha) that were once found a new soul mate is done with the next event, before the wedding ceremony consists of six stages, a wedding ceremony consists of 5 stages and after the wedding ceremony consists of two stages. Keywords: Procedures, society, Wedding, Nias, Onowaembo.